1992
DOI: 10.1159/000310315
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein-Angiographic Patterns in Patients with Central Serous Chorioretinopathy at the Initial Visit

Abstract: We reviewed the clinical records, color photographs and fluorescein angiograms of 106 eyes of 53 patients (44 men and 9 women) with central serous chorioretinopathy who had been followed up for 1 year or more. Their ages ranged from 20 to 59 years. One eye in each patient was involved at the initial visit. According to fluorescein-angiographic findings, the lesions were divided into smokestack pattern (13 eyes), ink blot appearance (33 eyes) and minimally enlarging spot (7 eyes). Most patients complained of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 8 publications
1
27
1
2
Order By: Relevance
“…In our study the commonest presenting complaint was blurring of vision (43.75%), followed by metamorphopsia (31.25%), relative scotoma (18.75%) and micropsia (6.25%) (Table2). Yamda, [5] et al studied 53 patients of central serous chorioretinopathy and the commonest presenting complaint in their study was relative scotoma (58%), followed by blurring of vision (34%), metamorphopsia (18%), micropsia (13.2%) and xanthopsia (5.7%), which is approximately similar to our study except that we found blurring of vision as the most common complaint and no patient in our study complained of xanthopsia. In our study out of 48 patients 7 had chronic central serous chorioretinopathy (duration more than 3 months) and 41 patients had acute central serous chorioretinopathy (Duration less than 2 weeks).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study the commonest presenting complaint was blurring of vision (43.75%), followed by metamorphopsia (31.25%), relative scotoma (18.75%) and micropsia (6.25%) (Table2). Yamda, [5] et al studied 53 patients of central serous chorioretinopathy and the commonest presenting complaint in their study was relative scotoma (58%), followed by blurring of vision (34%), metamorphopsia (18%), micropsia (13.2%) and xanthopsia (5.7%), which is approximately similar to our study except that we found blurring of vision as the most common complaint and no patient in our study complained of xanthopsia. In our study out of 48 patients 7 had chronic central serous chorioretinopathy (duration more than 3 months) and 41 patients had acute central serous chorioretinopathy (Duration less than 2 weeks).…”
Section: Discussionsupporting
confidence: 88%
“…1b) type of leak (Table-4). Yamda, [5] et al reported in their study, 62.2% inkblot type of leakage which is lower than our figure of 85.7% and 24.62% of smoke stack type which is higher than our figure of 14.28%. Majority of the eyes in our study (89.58%) showed a single leakage point, 8.33% eyes showed double leakage point and only one eye (1.785%) showed multiple leakage points.…”
Section: Discussioncontrasting
confidence: 84%
“…A Montero et al (5) made a study on 39 eyes and the mean visual acuity at baseline was 6/9 (range between 6/6 to 6/ 12) this is consistent with our study. Yameda et al (6) studied 106 eyes of 53 patients and the commonest complaint in their study was a central or paracentral scotoma (58.50%) followed by blurred vision (34%), metamorphopsia (18.90%), micropsia (13.20). Our study showed scotoma to be the second commonest complaint while rest of the symptomatology is quiet parallel to that in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Subretinal fluid moves downward under the influence of gravity, resulting in various shapes of sensory detachment such as tear, dumbbell, or flask [3,15,19,20]. Atrophic tract connecting posterior pole and inferior sensory detachment can be observed in some chronic cases, which can be more pronounced in FA and fundus autofluorescence (FAF) [21,32,33].…”
Section: Imaging For Diagnosis 41 Fundus Photographymentioning
confidence: 99%
“…The most common leaking pattern is an 'ink blot' pattern described by an early hyperfluorescent spot that gradually enlarges. The second most common leaking pattern (7-25%) is a 'smoke stack appearance' which is formed when dye passes into the subretinal space and ascends vertically to highest points and spreads laterally like umbrella or mushroom configuration until the entire area of serous detachment is filled (Fig 1) [32,33]. In acute forms, most cases had a single leakage site, rarely two or more [34].…”
Section: Fluorescein Angiographymentioning
confidence: 99%